Evidence for contamination with C. trachomatis in the household environment of children with active Trachoma: A cross-sectional study in Kongwa, Tanzania. - Sheila K West; Afshan A Nanji; Harran Mkocha; Beatriz Munoz; Charlotte Gaydos; Thomas C Quinn (PLoS Neglected Tropical Diseases)
Background Trachoma, a conjunctivitis caused by repeated infections with Chlamydia trachomatis, remains a significant cause of blindness worldwide. While mass treatments with azithromycin decreases disease and infection, re-emergence occurs, indicating that elimination may require other sustainable interventions. Environmental changes largely focus on facial hygiene and latrines, but further work to identify other possible transmission targets are needed. We sought to determine, in a cross-sectional survey of households of children with active trachoma, if we could detect the presence of Chlamydia trachomatis on household objects and on family members based on sleeping and caretaking patterns. Methods In five villages in Kongwa, Tanzania, children <five years were randomly chosen for examination for trachoma, and households of all children with active trachoma (n = 90) were eligible for this study. We administered structured questionnaires of sleeping and caretaking habits. Based on the responses, environmental swabs of bedding, furniture, clothing, and hands were taken and processed using Amplicor for detecting C. trachomatis DNA. Results Of 80 visited households, 13 (16%) had at least one swab from environmental sources positive for C. trachomatis DNA. A positive environmental swab was associated with the presence of ocular infection in the index child (Odds Ratio = 22.0, p = .007), the presence of an infant <1 year of age in the household, and whether the children's clothing had not been recently washed. Conclusions C. trachomatis DNA is present in the environment of children with active trachoma, especially in households with an ocular infection. Specific findings also suggest that washing hands, clothing, and bedding may be important.